Análisis de adopción de Metodologías Ágiles (Scrum, Kanban) para mejorar la eficiencia y calidad en el desarrollo de software en la Compañía Ingeniería Integrasayox S.A. - Álvarez Torres, Héctor Julio (2024)
This case study examines the implementation of agile methodologies, specifically Scrum and Kanban, in the company Ingeniería Integrasayox S.A., a company dedicated to software development. The main objective is to evaluate how these methodologies influence the efficiency and quality of software projects. The initial situation of the company, the challenges faced during the transition and the results obtained after the adoption of these methodologies are analyzed. The findings indicate significant improvements in project management, reduced delivery times, and increased customer satisfaction. The study also identifies best practices and lessons learned that can be applied by other companies in the sector.